Socialization Sorting, Waste Management, Waste Treatment In Selokerto Village, Sempor, Kebumen - Kusumastuti, Kusumastuti; Mutoharoh, Siti; Rahmadhani, Wulan; Dewi, Adinda Putri Sari (Prosiding University Research Colloquium, 2022)
Garbage is material that is disposed of as residue from industrial and household production. Garbage is the residue of human daily activities and/or natural processes in solid form (Law Number 81, 2012). The amount of waste produced in a certain area is proportional to the number of residents, types of activities, and the level of consumption of the population for goods or materials. The larger the population or the level of consumption of goods, the greater the volume of waste produced (Sucipto, 2012). Selokerto Village is one of the villages in Sempor sub-district with an area of 150 hectares. Based on preliminary results, it was found that most of the people of Selokerto are still not aware of environmental health with a classification of about 57% of residents throwing garbage and waste in rivers, 37% in the yard, 3% in the fields and 3% throwing garbage in its place. There needs to be concern from the Selokerto village community to minimize the existing waste into the Selokerto village environment. This community service was carried out by conducting socialization about waste management to the residents of Selokerto village which was attended by 30 people consisting of RW, RT, Kadus and cadres. Before and after the socialization, a pre-test and post-test of the residents’ knowledge about waste management were conducted. The results of the pre-test found that 60% of the residents did not know how to process waste. And after the socialization, the post test results showed that 80% of the residents had good knowledge of waste management. After the socialization, residents were also invited to do community service simultaneously in the Selokerto village area to maintain a clean environment. In conclusion, there is a need for public awareness and the need for waste management for the importance of maintaining environmental cleanliness in the Selokerto village area.